Radiation properties of a dielectric-loaded flanged parallel-plate waveguide with box-type termination - Chumachenko, VP; Sevgen, U (Urban & Fischer Verlag, 2001)
The domain product technique is used to study radiation properties of a hanged parallel-plate waveguide with a shaped radiating end incorporating a dielectric. The analysis is applied to obtain the reflection coefficient, radiation pattern and the aperture magnetic field in the case of a TEM mode excitation. It is found that a suitable choice of geometrical and physical parameters of the loading can ensure an excellent match of the waveguide to the free spate. The frequency band of the best match can be shifted in a desired manner along the frequency axis. The analysis also shows that the radiation pattern can he modified to a considerable extent by altering the geometry of the termination.
Keywords: aperture antennas; waveguide components; domain product technique